Requalificação do centro histórico da cidade de Santos – SP: programa “Alegra Centro” - Proença, Daniel Passos (2015)
Brazil is characterized as an essentially urban country, because more than 80% of the population lives in cities. By the end of the 20 th century, the Brazilian cities, mainly the large and medium ones, started to face problems of difficult solution as a consequence of the overpopulation in the urban centers. Urban centers, which usually shelter the historical and cultural heritage of the city, in other words, its memory, today is constituted by run down areas, harboring slums, deteriorated buildings, decadent commerce, among other problems that intensify the deconstruction of this space. The Statute of the City serves to equip the municipal districts, so that these can develop and execute their urban policies assuring the right to the sustainable city, which involves, among others, the protection, preservation and recovery of the environment as well as of the historical, cultural and landscape heritage. The present study analyzes how the partnership involving the government, the private sector and the estate owners, interacting with each other, destined for the users and the community, can revert the process of degradation of the historical centers through the “Alegra Centro” program, currently on the way in the city of Santos. This study can still be a contribution to revitalization programs of port areas.